Non-adhesive composition

A non-stick composition combining a fluorine-containing copolymer with a rubber or resin component addresses the challenge of low bioaccumulation and enhances mold release and repellency properties, achieving effective non-adhesive and water/oil-repellent performance.

JP7664842B2Active Publication Date: 2025-04-18UNIMATEC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021550349
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-03
Filing Date
2020-07-07
Publication Date
2025-04-18
Estimated Expiration
2040-07-07

AI Technical Summary

Technical Problem

Polymers with perfluoroalkyl groups having a carbon atom number of 6 or less exhibit low bioaccumulation properties, but existing compositions lack effective release properties and water and oil repellency.

Method used

A non-stick composition comprising a copolymer of a fluorine-containing copolymer and a rubber component or resin, where the fluorine-containing copolymer has a specific structure and is present in a specific mass ratio, enhancing mold release properties and water and oil repellency.

Benefits of technology

The composition achieves excellent mold release properties and water and oil repellency, allowing for easy removal from molds and low adhesion to other materials, making it suitable for various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007664842000001
    Figure 0007664842000001
  • Figure 0007664842000002
    Figure 0007664842000002
  • Figure 0007664842000003
    Figure 0007664842000003
Patent Text Reader

Abstract

Provided is a non-adhesive composition that exhibits excellent release properties, water repellency and oil repellency. This non-adhesive composition contains a rubber component or a resin and a fluorine-containing copolymer at a quantity of 0.05-10 parts by mass relative to 100 parts by mass of the rubber component or resin. The fluorine-containing copolymer is a copolymer of: a fluoroalkyl alcohol (meth)acrylic acid derivative; and a (meth)acrylic ester, a fumaric acid monoalkyl ester or dialkyl ester, or a maleic acid monoalkyl ester or dialkyl ester.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-stick composition. [Background technology]

[0002] 2. Description of the Related Art Polymers having perfluoroalkyl groups have been considered promising for use in a variety of applications due to their excellent properties.

[0003] Patent Document 1 (WO 2004 / 035708) discloses a water / oil repellent composition comprising, as an essential component, a copolymer containing polymerized units of a monomer (a) having a polyfluoroalkyl group, and polymerized units of other monomers, wherein the melting point of microcrystals derived from the polyfluoroalkyl group of the homopolymer of the monomer is absent or is 55°C or lower, and the glass transition point of the homopolymer is present and is 20°C or higher.

[0004] Patent Document 2 (WO 2009 / 034773) discloses a fluorine-containing copolymer of (a) a fluoroalkyl alcohol acrylic acid derivative or a corresponding methacrylic acid derivative and (b) an acrylic acid ester or methacrylic acid ester, a monoalkyl ester or dialkyl ester of fumaric acid or maleic acid, or a vinyl ester. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2004 / 035708 [Patent Document 2] International Publication No. 2009 / 034773 Summary of the Invention [Problem to be solved by the invention]

[0006] Among polymers having perfluoroalkyl groups, those having a perfluoroalkyl group with 6 or less carbon atoms have low bioaccumulation potential, and therefore their usefulness has been attracting attention in various technical fields. Development of a composition containing a polymer having a perfluoroalkyl group with 6 or less carbon atoms and other components has been considered.

[0007] The present inventors discovered that a composition containing a copolymer of a specific structure having a perfluoroalkyl group having 6 or less carbon atoms and a rubber component or a resin has excellent releasability and water and oil repellency, and thus arrived at the present invention. That is, the present invention provides a non-adhesive composition having excellent releasability and water and oil repellency. [Means for solving the problem]

[0008] The gist and configuration of the present invention are as follows. [1] A rubber component or resin, The rubber component or resin contains 0.05 to 10 parts by mass of a fluorine-containing copolymer based on 100 parts by mass of the resin, The fluorine-containing copolymer is C n F 2n+1 (CH2CF2) a (CF2CF2) b (CH2CH2) c OCOCR 1 =CH2(wherein, R 1 represents a hydrogen atom or a methyl group, n represents an integer of 1 to 6, a represents an integer of 1 to 4, b represents an integer of 1 to 3, and c represents an integer of 1 to 3), R 2 OCOCR 1 =CH2(wherein, R 1 is a hydrogen atom or a methyl group, R 2 represents an alkyl group, an alkoxyalkyl group, a cycloalkyl group, an aryl group, or an aralkyl group), a (meth)acrylic acid ester, a monoalkyl ester or dialkyl ester of fumaric acid, or a monoalkyl ester or dialkyl ester of maleic acid; A non-adhesive composition comprising a copolymer of [2] The non-adhesive composition according to the above [1], wherein the weight average molecular weight of the fluorine-containing copolymer is 2,000 to 50,000. Effect of the Invention

[0009] It is possible to provide a non-adhesive composition having excellent releasability and water and oil repellency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] (Non-adhesive composition) The non-tacky composition of the present invention contains a rubber component or resin and 0.05 to 10 parts by mass of a fluorine-containing copolymer per 100 parts by mass of the rubber component or resin. The fluorine-containing copolymer is a copolymer of the following monomers (a) and (b): (a)C n F 2n+1 (CH2CF2) a (CF2CF2) b (CH2CH2) c OCOCR 1 =CH2(wherein, R 1 represents a hydrogen atom or a methyl group, n represents an integer of 1 to 6, a represents an integer of 1 to 4, b represents an integer of 1 to 3, and c represents an integer of 1 to 3), (b)R 2 OCOCR 1 =CH2(wherein, R 1 is a hydrogen atom or a methyl group, R 2 represents an alkyl group, an alkoxyalkyl group, a cycloalkyl group, an aryl group, or an aralkyl group), a monoalkyl ester or dialkyl ester of fumaric acid, or a monoalkyl ester or dialkyl ester of maleic acid. The monomer (a) "fluoroalkyl alcohol (meth)acrylic acid derivative" refers to a fluoroalkyl alcohol acrylic acid derivative or a fluoroalkyl alcohol methacrylic acid derivative. The monomer (b) "(meth)acrylic acid ester" refers to an acrylic acid ester or a methacrylic acid ester.

[0011] The non-adhesive composition of the present invention comprises a perfluoroalkyl group C having 6 or less carbon atoms in a fluorocopolymer. n F 2n+1 (n is an integer of 1 to 6) and a rubber component or resin. Perfluoroalkyl groups having 6 or less carbon atoms have low bioaccumulation properties, and therefore can enhance safety to the human body. In addition, since the fluorine-containing copolymer contains a hydrocarbon portion, it has excellent compatibility with rubber components and resins, and even when it contains 0.05 to 10 parts by mass per 100 parts by mass of the rubber component or resin, it can be uniformly dispersed or dissolved in the rubber component or resin. Therefore, for example, when the non-adhesive composition containing the rubber component and the fluorine-containing copolymer of the present invention is filled into a mold and then vulcanized to form a mold, the fluorine-containing copolymer exudes onto the surface of the non-adhesive composition during the molding to form a low-energy surface. Similarly, when the non-adhesive composition containing the resin and the fluorine-containing copolymer of the present invention is filled into a mold and then crosslinked, polymerized, or the like to form a mold, the fluorine-containing copolymer exudes onto the surface of the non-adhesive composition during the molding to form a low-energy surface. As a result, the molded product obtained by molding the non-adhesive composition can be easily removed from the mold. In addition, the obtained molded product also has low adhesion to other materials on its surface, so it can have properties such as non-adhesiveness, water repellency, and oil repellency. Therefore, the molded product can be used in products that require these properties. More specifically, the molded product of the non-sticky composition of the present invention can be used for rubber products such as fluororubber, natural rubber, EPDM rubber, and acrylic rubber, resin products such as acrylic resin, vinyl chloride resin, epoxy resin, polyurethane resin, and phenolic resin, waterproof sealant (modified silicone), non-stickiness, water repellency, and stain prevention of nonwoven fabric, and as an internal mold release agent during molding.

[0012] Examples of the rubber component constituting the non-tacky composition of the present invention include fluororubber, natural rubber, EPDM rubber, urethane rubber, acrylic rubber, and hydrin rubber. The fluororubber is not particularly limited, and examples thereof include vinylidene fluoride fluororubber (FKM), tetrafluoroethylene-propylene fluororubber (FEPM), and tetrafluoroethylene-purple vinyl ether fluororubber (FFKM). The rubber component may be either an uncrosslinked or crosslinked rubber component, but is preferably a crosslinked rubber component. The crosslinked rubber component may be a rubber component after either primary crosslinking or secondary crosslinking. The fluororubber is distinguished from the fluorocopolymer of the present invention in that it does not contain the monomer (b). In addition, examples of the resin constituting the non-tacky composition of the present invention include fluororesin, epoxy resin, phenol resin, melamine resin, polyethylene resin, polypropylene resin, polyester resin, and vinyl chloride resin. The fluororesin is distinguished from the fluorocopolymer of the present invention in that it does not contain the monomer (b).

[0013] The content of the fluorine-containing copolymer in the non-adhesive composition of the present invention is 0.05 to 10 parts by mass, preferably 0.05 to 5.0 parts by mass, more preferably 0.05 to 2.0 parts by mass, and even more preferably 0.05 to 1.0 parts by mass, based on 100 parts by mass of the rubber component or resin. When the content of the fluorine-containing copolymer is within the above range, the surface can be modified to be non-adhesive. The weight-average molecular weight of the fluorine-containing copolymer is preferably 2000 to 50000, more preferably 2000 to 20000, and even more preferably 3000 to 10000. When the weight-average molecular weight of the fluorine-containing copolymer is within the above range, the non-adhesive fluorine-containing copolymer can migrate to the surface of the rubber component or resin. The weight-average molecular weight Mw of the fluorine-containing copolymer can be measured by gel permeation chromatography (GPC).

[0014] The molar ratio of the monomers (a) and (b) constituting the fluorine-containing copolymer is not particularly limited, but the monomer (a):(b) (molar ratio) is preferably 10:1 to 1:100, more preferably 5:1 to 1:50, and even more preferably 2:1 to 1:40. When the molar ratio of the monomers (a) and (b) is within the above range, the non-adhesive fluorine-containing copolymer can migrate to the surfaces of various rubber components or resins.

[0015] With respect to n, a, b, and c in the monomer (a), n is preferably 2 to 4, more preferably 4, a is preferably 1 to 2, more preferably 2, b is preferably 1 to 2, and c is preferably 1 to 2. Specific examples of the monomer (a) include 3,3,4,4,5,5,6,6,7,7,9,9,10,10,11,11,12,12,12-nonadecafluorododecyl acrylate, 3,3,4,4,5,5,6,6,7,7,9,9,10,10,11,11,12,12,12-nonadecafluorododecyl methacrylate, and monomers of the following structural formulas. [ka]

[0016] R in the above monomer (b) in the fluorine-containing copolymer 2is an alkyl group, an alkoxyalkyl group, a cycloalkyl group, an aryl group, or an aralkyl group, and examples of such groups include alkyl groups such as methyl, ethyl, propyl, isopropyl, n-butyl, n-hexyl, 2-ethylhexyl, n-octyl, lauryl, and stearyl, alkoxyalkyl groups such as methoxymethyl, 2-methoxyethyl, 2-ethoxyethyl, 2-butoxyethyl, and 3-ethoxypropyl, cycloalkyl groups such as cyclohexyl, aryl groups such as phenyl, and aralkyl groups such as benzyl. Examples of monoalkyl esters or dialkyl esters of fumaric acid include monomethyl, dimethyl, monoethyl, diethyl, monopropyl, dipropyl, monobutyl, dibutyl, mono 2-ethylhexyl, di 2-ethylhexyl, monooctyl, and dioctyl monoalkyl esters of fumaric acid. Examples of monoalkyl esters or dialkyl esters of maleic acid include monomethyl, dimethyl, monoethyl, diethyl, monopropyl, dipropyl, monobutyl, dibutyl, mono 2-ethylhexyl, di 2-ethylhexyl, monooctyl, dioctyl, etc. Specific examples of monomer (b) include vinyl esters such as 2-ethylhexyl methacrylate, lauryl methacrylate, cetyl methacrylate, stearyl methacrylate, behenyl methacrylate, cyclohexyl acrylate, lauryl acrylate, cetyl acrylate, stearyl acrylate, behenyl acrylate, vinyl acetate, vinyl caprylate, etc., and monomers having the structural formula shown below. [ka]

[0017] The rubber component may contain, as additives other than rubber, a crosslinking agent, a crosslinking accelerator, an acid acceptor, a filler, etc. The resin may contain a polymerization initiator, a filler, etc.

[0018] The monomer (a) can be produced by esterification of a fluoroalkyl alcohol with acrylic acid or methacrylic acid. The fluoroalkyl alcohol can also be produced from the corresponding fluoroalkyl iodide. The fluoroalkyl alcohol can be produced by first reacting the fluoroalkyl iodide with N-methylformamide HCONH(CH3) to produce a mixture of the fluoroalkyl alcohol and its formate, and then hydrolyzing the mixture in the presence of an acid catalyst.

[0019] The fluorine-containing copolymer of the present invention can be prepared, for example, as follows: A polymerization reaction of monomers (a) and (b) is carried out in the following solvents: fluorine-containing organic solvents such as 1,4-bis(trifluoromethyl)benzene, 1,1,1,2,2-pentafluoro-3,3-dichloropropane, 1,1,2,2,3-pentafluoro-1,3-dichloropropane, 1,1,1,2,3,4,4,5,5,5-decafluoropentane, and perfluorohexane; ester-based solvents such as methyl acetate, ethyl acetate, propyl acetate, butyl acetate, and methyl acetate propionate; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, 2-pentanone, 3-pentanone, and 2-hexanone; and solvents such as acetonitrile, dimethylformamide, diethylformamide, dimethylacetamide, and N-methyl-2-pyrrolidone.

[0020] When carrying out the polymerization reaction of the fluorine-containing copolymer, a polymerization initiator can be used in an amount of preferably 0.1 to 4 parts by mass, more preferably 1 to 2 parts by mass, based on 100 parts by mass of the total amount of the monomers (a) and (b). As the polymerization initiator, diacyl peroxide, peroxycarbonate, peroxyester, etc. can be used. More specifically, as the polymerization initiator, organic peroxides such as isobutyryl peroxide, lauroyl peroxide, stearoyl peroxide, succinic acid peroxide, bis(heptafluorobutyryl) peroxide, pentafluorobutyroyl peroxide, bis(4-tert-butylcyclohexyl) peroxydicarbonate, di-n-propyl peroxydicarbonate, diisopropyl peroxydicarbonate, etc., azo compounds such as azobisisobutyronitrile, inorganic peroxides, or redox systems thereof can be used. In addition, a polymerization initiator may be added during the polymerization reaction as necessary.

[0021] In order to adjust the weight average molecular weight of the fluorine-containing copolymer, a chain transfer agent can be used as necessary. Examples of the chain transfer agent include n-dodecyl mercaptan, dimethyl ether, methyl tert-butyl ether, C1 to C6 alkanes, methanol, ethanol, 2-propanol, cyclohexane, carbon tetrachloride, chloroform, dichloromethane, methane, ethyl acetate, ethyl malonate, and acetone.

[0022] The copolymerization reaction for obtaining the fluorine-containing copolymer can be carried out at a temperature of preferably 0 to 100°C, more preferably 5 to 60°C, and even more preferably 40 to 50°C. Typically, after the polymerization reaction is completed, a copolymer solution having a solid content concentration of 5 to 50 mass% is obtained, and the fluorine-containing copolymer can be obtained by removing the solvent from this copolymer solution. The fluorine-containing copolymer is separated from the copolymer solution by a method of evaporating the copolymer solution to dryness, or a method of adding a flocculant such as an inorganic salt to the copolymer solution to flocculate the fluorine-containing copolymer, and then purified by a method of washing with a solvent or the like.

[0023] (Method for producing non-adhesive composition) The non-tacky composition of the present invention can be obtained by mixing the fluorocopolymer prepared as described above with a rubber component or a resin. The non-tacky composition of the present invention may be obtained by mixing the raw materials for the rubber component or the resin with the fluorocopolymer and then subjecting the mixture to treatment such as vulcanization or heating.

[0024] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and includes all aspects included in the concept of the present invention and the scope of the claims, and can be modified in various ways within the scope of the present invention. EXAMPLES

[0025] Next, in order to further clarify the effects of the present invention, examples will be described, but the present invention is not limited to these examples.

[0026] <Preparation of Fluorine-Containing Copolymer> A fluorine-containing copolymer was prepared as follows.

[0027] (Fluorine-containing copolymer 1) 1.7 g of DTFAC-103 (3,3,4,4,5,5,6,6,7,7,9,9,10,10,11,11,12,12,12-nonadecafluorododecyl acrylate; monomer (a)), 32.9 g of StAc (stearyl acrylate; monomer (b)), 46.8 g of MEK (methyl ethyl ketone; solvent), 1.5 g of AIBN (azobisisobutyronitrile; polymerization initiator), and 1.7 g of NDMC (n-dodecyl mercaptan; chain transfer agent) were charged into a 200 ml glass reactor equipped with a condenser and a thermometer, and the polymerization reaction of DTFAC-103 and StAc was carried out at 68 ° C. for 16 hours with stirring, to obtain 81.5 g of a copolymer solution with a solid content concentration of 40.5 mass %. The obtained copolymer solution was reprecipitated in methanol, and the solvent was removed in an oven at 120°C to obtain fluorocopolymer 1 having DTFAC-103 and StAc as monomers. The weight average molecular weight Mw of the obtained fluorocopolymer 1 was measured by GPC and found to be 8200. The blending amounts of the raw materials, the recovered amount of the copolymer solution, the solids concentration of the copolymer solution, and the weight average molecular weight of fluorocopolymer 1 are shown in Table 1.

[0028] (Fluorine-containing copolymer 2~7) Fluorine-containing copolymers 2 to 7 were prepared in the same manner as for fluorine-containing copolymer 1, except that the amounts and types of raw materials were changed as shown in Table 1. Table 1 shows the recovered amount of the copolymer solution when fluorine-containing copolymers 2 to 7 were prepared, the solids concentration of the copolymer solution, and the weight-average molecular weight of fluorine-containing copolymers 2 to 7.

[0029] [Table 1] The symbols in Table 1 represent the following substances. DTFAC-103: 3,3,4,4,5,5,6,6,7,7,9,9,10,10,11,11,12,12,12-nonadecafluorododecyl acrylate (monomer (a)), DTFMAC-103: 3,3,4,4,5,5,6,6,7,7,9,9,10,10,11,11,12,12,12-nonadecafluorododecyl methacrylate (monomer (a)), StAc: stearyl acrylate (monomer (b)), MEK: methyl ethyl ketone (solvent); AIBN: Azobisisobutyronitrile (polymerization initiator), NDMC: n-dodecyl mercaptan (chain transfer agent).

[0030] (Examples 1 to 7 and Comparative Examples 1 to 2) The materials were kneaded in the amounts shown in Table 2 below with an open roll to obtain a kneaded product. The obtained kneaded product was subjected to Mooney viscosity measurement, and the scorch time (t5) at 125°C was measured in accordance with ISO 289. Next, press vulcanization (primary vulcanization) was performed at 180°C for 10 minutes, and then oven vulcanization (secondary vulcanization) was performed at 230°C for 22 hours. The compression set at 200°C for 70 hours was measured for each crosslinked molded product obtained in this manner using a P-24 O-ring in accordance with ASTM D395, Method B. In addition, hardness, breaking strength, and breaking elongation were measured in accordance with ISO 37 and ISO 7619-1 Type1A. The vulcanization conditions and the above measurement results are shown in Table 2.

[0031] After obtaining the kneaded products of each example as described above, a test for evaluating releasability was carried out as follows. The kneaded products were placed in an O-ring mold of a mold release evaluation machine, and then primary vulcanization was carried out at 205°C for 3 minutes. The releasability of the crosslinked molded product when it was removed from the mold after primary vulcanization was visually evaluated according to the following criteria. ◯: The crosslinked molding was neither stuck to the inside of the mold nor damaged, and the crosslinked molding could be smoothly released from the mold. Δ: Some adhesion of the crosslinked molding to the inside of the mold was observed, but the crosslinked molding could be released from the mold. ×: When the crosslinked molding was released from the metal mold, the crosslinked molding was significantly damaged and was difficult to release. The evaluation results of the releasability are shown in Table 2 below.

[0032] [Table 2]

[0033] The results in Table 2 show that the non-adhesive composition of the present invention has excellent releasability. On the other hand, the composition of Comparative Example 1 did not contain the fluorine-containing copolymer of the present invention, and therefore the releasability was "x". Moreover, the composition of Comparative Example 2 contained a fluorine-based processing aid with a different chemical structure from the fluorine-containing copolymer of the present invention, and therefore the releasability was "Δ".

[0034] Example 8 100 parts by mass of polyurethane prepolymer (Coronate (registered trademark) C-4090 (trade name); manufactured by Nippon Polyurethane Industry Co., Ltd.) heated to 80 ° C., 12.8 parts by mass of methylene bis-o-chloroaniline curing agent (Iharakyuamine MT (trade name); manufactured by Kumiai Chemical Industry Co., Ltd.) melted by heating, and 1.0 part by mass of the fluorine-containing copolymer 1 prepared above were stirred and mixed while avoiding the inclusion of air bubbles to obtain a mixture. Then, the mixture was poured into an aluminum mold (diameter 45 mm, depth 50 mm). A hook for removing the cured molded product was set up in the center of the cavity of the mold, and the mixture was heated and cured at 120 ° C. for 1 hour, after which the obtained molded product was removed from the mold by pulling the hook. The release load at this time was 15 N.

[0035] The materials were mixed and stirred in the same manner as in Example 8 to obtain a mixture, which was then applied to a stainless steel plate (2 x 5 cm) and then heat cured at 120°C for 1 hour. The static and dynamic contact angles (using the Cecil drop method), which are an index of water and oil repellency, of the obtained test specimens were measured for water and hexadecane. The measurement results of water and oil repellency are shown below. Water repellency: static contact angle of water 112°, water sliding angle (dynamic contact angle) 4° Oil repellency: Static contact angle of hexadecane: 40°, sliding angle (dynamic contact angle) of hexadecane: 2°.

[0036] Comparative Example 3 100 parts by mass of polyurethane prepolymer (Coronate (registered trademark) C-4090 (trade name); manufactured by Nippon Polyurethane Industry Co., Ltd.) heated to 80 ° C. and 12.8 parts by mass of methylene bis-o-chloroaniline curing agent (Iharakyuamine MT (trade name); manufactured by Kumiai Chemical Industry Co., Ltd.) melted by heating were stirred and mixed to obtain a mixture while avoiding the inclusion of air bubbles. The mixture was poured into an aluminum mold (diameter 45 mm, depth 50 mm). A hook for removing the cured molded product was set up in the center of the cavity of the mold, and the mixture was heated and cured at 120 ° C. for 1 hour, after which the obtained molded product was removed from the mold by pulling the hook. The mold release load at this time was 100 N or more, and the molded product could not be removed from the mold.

[0037] In the same manner as in Example 8, the mixture of Comparative Example 3 was applied to a stainless steel plate (2 x 5 cm), and then the mixture was heat cured at 120°C for 1 hour. For the obtained test piece, the static contact angle and dynamic contact angle, which are an index of water and oil repellency (using the Cecil drop method), were measured for water and hexadecane. The measurement results of water and oil repellency are shown below. Water repellency: static contact angle of water 69°, water sliding angle (dynamic contact angle) 54° Oil repellency: static contact angle of hexadecane: 8°, sliding angle of hexadecane (dynamic contact angle): hexadecane adhered to the surface of the test piece and could not be measured.

[0038] From the above Example 8 and Comparative Example 3, it can be seen that the non-adhesive composition of the present invention has a low demolding load and excellent demolding properties. Furthermore, compared to Comparative Example 3, in Example 8, the static contact angle of water is large, the dynamic contact angle of water is small, and the static contact angle of hexadecane is large, and no adhesion of hexadecane to the test piece was observed during dynamic contact angle measurement. Therefore, it can be seen that the molded product of the non-adhesive composition of the present invention has excellent water and oil repellency.

Claims

1. A rubber component or a resin, The rubber component or resin contains 0.05 to 10 parts by mass of a fluorine-containing copolymer based on 100 parts by mass of the resin, The fluorine-containing copolymer is Monomer (a), C n F 2n+1 (CH 2 CF 2 ) a (CF 2 CF 2 ) b (CH 2 CH 2 ) c OCOCR 1 =CH 2 (In the formula, R 1 represents a hydrogen atom or a methyl group, n represents an integer of 1 to 6, a represents an integer of 1 to 4, b represents an integer of 1 to 3, and c represents an integer of 1 to 3), Monomer (b), R 2 OCOCR 1 =CH 2 (In the formula, R 1 is a hydrogen atom or a methyl group, R 2 represents an alkyl group, an alkoxyalkyl group, a cycloalkyl group, an aryl group, or an aralkyl group), a (meth)acrylic acid ester, a monoalkyl ester or dialkyl ester of fumaric acid, or a monoalkyl ester or dialkyl ester of maleic acid; is a copolymer of The weight average molecular weight of the fluorine-containing copolymer is 3,000 to 10,000, The non-tacky composition, wherein the rubber component or resin is a fluororubber or a fluororesin.

2. The non-adhesive composition described in claim 1, wherein the rubber component or resin is a fluororubber.

Citation Information

Patent Citations

  • Water-and-oil repellant composition

    WO2004035708A1

  • Fluorine-containing polymer and surface modifier containing the same as active ingredient

    WO2009034773A1